FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA HOUSEKEEPING DEPARTMENT DI HOTEL IBIS PEKANBARU - Arianda, Ari; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study aims to determine how the faktors that effect the peforrmance of the housekeeping department at the ibis hotel pekanbaru this research used descriptive quantitative method analyz the programs. The sample in the study of 20 respondents ware taken by using observasion, quesioner, and documentation. By using a likert scale as a measure to determine the length of the short interval.Base on the result of, responden to the faktors that effect the performance of housekeeping department at the hotel ibis pekanbaru,are namely organizational factors, individual faktors and social faktors. Where the organizational faktors that most influence significanly.Key words : Affect performance, Housekeeping Department, Ibis Riau